Gun ownership, poverty, and mental health associations with crime: A cross-state comparison - Smith, Sven (Criminology & criminal justice, 2023)
Violent crime is a concern in the United States. Past research has suggested different correlates, including poverty, mental health disorders and the presence of guns. One particular theory, named the facilitation hypothesis, states that firearms enhance the power of an aggressor, they reduce the necessity of a physical attack, and encourage those who may not otherwise resort to violence. We look at various social factors and their relationship regarding different indicators of violent crime. We find that at the state level, gun ownership is correlated with violent crimes and income inequality with homicides specifically and we find support for the facilitation hypothesis. Future public policies which target these issues appear likely to bear fruit toward the goal of reducing crime.